Environmentally Efficient Weil-Being: Rethinking Sustainability as the Relationship between Human Well-being and Environmental Impacts - Dietz, T; Rosa, E A; York, R (Human ecology review, 2009)
The question of how to measure sustainability remains vexing. We approach the problem by noting that most theories of environmental impact assume that exploitation of the environment provides benefits to human well-being. However, this assumption has not been subject to much empirical discipline. We propose a model of Efficient Weil-Being (EWEB) inspired by the Stochastic Frontier Production Models commonly used in economics. EWEB assesses a nation-state's efficiency in enhancing human well-being through the use of economic, natural and human resources. This approach shifts attention from the elusive question of whether a nation is sustainable to the more tractable question of how efficient a nation is in producing human well-being. We model human well-being as a function of physical, natural and human capital. In a preliminary test of this approach here we opera-tionalize human well-being as life expectancy, flows of physical capital as gross domestic product per capita, flows of natural capital as the ecological footprint, and human capital as education. Using data from 135 nations, we find that controlling for physical and human capital, exploitation of the environment has no net effect on well-being. This suggests that improvements in well-being may be attainable without adverse effects on the environment. We also find that many nations could substantially improve their efficiency in using human and natural resources to generate well-being.